Study of Health Economics towards Accelerating Economic Growth: Exploring the Impact of Health on Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2022)
We drew our numbers from the State Bank of India, the World Development Indicators, and theEconomic Survey of India. It is worthwhile, before moving on to the empirical model of economic growth,to investigate the role that TFP plays in fostering expansion when health is present as a kind of humancapital. Among the collection of explanatory factors that determine India's GDP per capita, health, labor,and RD emerge as the most important, as shown by the regression findings. While a positivecorrelation between physical capital and GDP growth was found, it was not statistically significant. Thisfinding, significant at the 1 level, lends credence to the idea that improved health contributes to aflourishing economy. Based on information from 64 research totaling 719 estimations from across fourcontinents, this study tries to analyze the effect of health on economic growth Four Continents Asian,European, American, and African.